1997
DOI: 10.1093/toxsci/40.1.68
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Acute and Repeated Exposures to Aroclor 1254 in Adult Rats: Motor Activity and Flavor Aversion Conditioning

Abstract: demonstrate that Aroclor 1254 causes hypoactivity and flavor Effects of Acute and Repeated Exposures to Aroclor 1254 in aversions in adult rats; the no observable effect level (NOEL) for Adult Rats: Motor Activity and Flavor Aversion Conditioning. motor activity was 100 mg/kg for acute exposure and 10 mg/kg Nishida, N., Farmer, J. D., Kodavanti, P. R. S., Tilson, H. A., and for repeated exposure for a period of up to 6 weeks. Polychlorinated biphenyls (PCBs) have been identified as days old) were tested for mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

1999
1999
2003
2003

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 0 publications
2
8
0
Order By: Relevance
“…Assessment of motor coordination with two tests ( screen test and rotor rod ) did not reveal any significant effect 15 -120 min after treatment with a single dose of 500 mg / kg of Aroclor 1254. Similar results regarding a decrease in spontaneous motor activity were reported in adult male Long-Evans rats following single gavage doses of 300 mg / kg of Aroclor 1254; no significant effect was seen with 100 mg / kg ( Nishida et al, 1997 ). Incomplete recovery to pretreatment levels of activity occurred over a 9 -week period.…”
Section: Oral Exposuresupporting
confidence: 82%
See 1 more Smart Citation
“…Assessment of motor coordination with two tests ( screen test and rotor rod ) did not reveal any significant effect 15 -120 min after treatment with a single dose of 500 mg / kg of Aroclor 1254. Similar results regarding a decrease in spontaneous motor activity were reported in adult male Long-Evans rats following single gavage doses of 300 mg / kg of Aroclor 1254; no significant effect was seen with 100 mg / kg ( Nishida et al, 1997 ). Incomplete recovery to pretreatment levels of activity occurred over a 9 -week period.…”
Section: Oral Exposuresupporting
confidence: 82%
“…Kodavanti et al (1998 ) also reported decreased motor activity in adult male rats exposed to 30 mg / kg/day of Aroclor 1254 for 4 weeks. Nishida et al ( 1997) also conducted flavor-aversion conditioning tests and reported that the acute and repeated NOAELs for this behavioral test were 15 and 7.5 mg /kg, respectively. Freeman et al (2000 ) conducted a 52 -week feeding study in rats with various Aroclor mixtures ( 1016,1242,1254,1260 ) and found no significant treatment-related effects on a comprehensive number of neurological end points.…”
Section: Oral Exposurementioning
confidence: 99%
“…In addition, numerous studies have shown that PCBs cause alterations in motor behaviors in developing and adult mammals [Bowman et al, 1978;Chou et al, 1979;Nishida, 1997;Rosin and Martin, 1981;Schantz et al, 1991;Tilson et al, 1990].…”
Section: Gross Morphology and Swimming Behaviormentioning
confidence: 99%
“…PCBs cause a variety of adverse effects on the nervous system, including altered memory and learning, motor deficits, and neurodevelopmental delays [Brouwer et al, 1995;Nishida, 1997;Seegal et al, 1990;Stewart et al, 2000]. In addition, the dopaminergic neurotransmitter system, which plays an integral role in controlling motor behaviors, is altered by PCBs [Agrawal et al, 1981;Contreras, 1994, 1996;Bemis and Segal, 1999;Seegal et al, 1990].…”
Section: Gene Expression Signature Patternsmentioning
confidence: 99%
“…They were treated via oral gavage with corn oil (2 mL/kg). Dose levels were chosen based on the results of Nishida et al (26) because that experiment was conducted successfully using the more potent lot 6024. The doses for lot 124-191 were 0, 10, 30, 100, 300, or 1,000 mg/kg body weight, and the doses for lot 6024 were 0, 1, 3, 10, 30, 100, 300, or 1,000 mg/kg body weight.…”
Section: Methodsmentioning
confidence: 99%